Statistical analysis using Excel LiveLessons. - Carlberg, Conrad (LiveLessons (Indianapolis, Ind.), 2013)
"Statistical Analysis Using Excel Volume II LiveLessons provides over 9 hours of video instruction. Means, medians and modes are one thing. Multiple regression analysis is quite another! These training videos bring it into focus. Bestselling author and experienced consultant Conrad Carlberg provides the novice with 9+ hours of hands-on step-by-step video training on the intricacies that comprise statistical analysis. This Volume II series moves from the basics to intermediate applications and how Excel supports them: for example, the Analysis of Variance (ANOVA) and how it's supported simplistically by the Data Analysis add-in, and more powerfully by worksheet functions such as LINEST and by the combination of effect coding with Excel's lookup functions. This volume concludes with discussions and demonstrations of more advanced techniques, showing how multiple regression combines with the General Linear Model to produce the analysis of covariance, and how Excel's mixed referencing makes it easy to visualize what's going on as new vectors enter an analysis."--Resource description page.